PERLINDUNGAN HUKUM TERHADAP HAK ASASI KARYAWAN UNTUK MELAKSANAKAN PERINTAH AGAMA DAN KEPERCAYAANNYA DI TEMPAT KERJA (STUDI KASUS PT. MATAHARI DEPT. STORE, TBKMALANG RAYA) - Tri Neneng Lilis Rahayu (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2018)
Human Rights is rights inherent to every human without which it is imposible for him/her to live asa human. The deed made by the entrepreneur who added rule about the prohibition of hijab for female workers can be categorized as a treatment of discrimination against workers based on on the basic of religion. In connection with this matter, articles 5 and 6 of the law number 13 years of 2003 on Employment, wearing the hijab is a form of worship that is a part of Religion Human Rights. The right to religion itself is stated in article 28E verses 1 and 2 of 1945 Constitution and reinforced in article 22 of the law No. 39 year of 1999 on Human Rights, herewith referred to the law on human rights. The purpose of this study is to determine whether or not there is a violation of human rights in the implementation of religious orders and belief in PT. Matahari Dept. Store, Tbk Malang. It is a socio-juridical research type employing a descriptive-qualitative method in the analysis. The data obtained from the field were then analyzed and described in a detailed way. Keywords: Legal Protection, Employee’s Human Rights, Labour